The Role of LSP P3 Junior Spa Therapist Competency Certification on Work Readiness and Absorption of the Tourism Industry - Nawanksari, Septiari; Sudira, Putu; Mutohhari, Farid (Journal of Education Technology, 2021)
The tourism industry, which is a promising sector for the spa business, does not only require hard skill competencies, but also requires mature work readiness and high absorption. LSP P3 competency certification is one of the important programs to improve work readiness and labor absorption of spa therapists in the tourism industry. This study aims to analyze how much influence the competence certification of Junior Spa Therapist LSP P3 on Asesi's work readiness and Asesi's absorption in the tourism industry in the spa sector. Ex-post facto research with a quantitative approach. A total of 66 respondents of spa therapists were included in this study as a sample. Data were collected through a questionnaire with a 4 Likert scale questionnaire instrument. Data analysis was performed using regression analysis and SEM analysis. The results showed that the LSP P3 Junior Spa Therapist competency certification had a significant effect on Asesi's work readiness and Asesi's absorption in the tourism industry in the spa sector. The competency certification program must further improve the quality of its implementation. Education and training institutions must organize various competency certification programs that are even more optimal, especially when competency tests must be carried out intensively in accordance with the perceptions of the spa therapist workers.